Editorial - Astrid Gynnild (Grounded Theory Review: An International Journal)
Ideas are precious. They may come to mind when you least expect to them to, and many times before you are consciously aware of them. The grounded theory solution to capturing valuable ideas from preconscious thought is writing memos. In this issue of the Grounded Theory Review, we are delighted to publish the first chapter of Barney G. Glaser’s coming book on memoing, which truly opens up new perspectives on the potentially complex but productive process of collecting ideas that is such an important part of doing grounded theory.